Twelve weeks supplementation with an extended-release caffeine and ATP-enhancing supplement may improve body composition without affecting hematology in resistance-trained men. Issue 1 (December 2016) - Joy, Jordan; Vogel, Roxanne; Moon, Jordan; Falcone, Paul; Mosman, Matt; Kim, Michael
Abstract Background Increased ATP levels may enhance training-induced muscle accretion and fat loss, and caffeine is a known ergogenic aid. A novel supplement containing ancient peat and apple extracts has reported enhanced mitochondrial ATP production and it has been coupled with an extended-release caffeine. Therefore, the purpose of this investigation was to determine the effects of this supplement on body composition when used in conjunction with 12 weeks of resistance training. Methods Twenty-one resistance-trained subjects (27.2 ± 5.6y; 173.5 ± 5.7 cm; 82.8 ± 12.0 kg) completed this study. Subjects supplemented daily with either 1 serving of the supplement (TRT), which consisted of 150 mg ancient peat and apple extracts, 180 mg blend of caffeine anhydrous and pterostilbene-bound caffeine, and 38 mg B vitamins, or an equal-volume, visually-identical placebo (PLA) 45 min prior to training or at the same time of day on rest days. Supervised resistance training consisted of 8 weeks of daily undulating periodized training followed by a 2-week overreach and a 2-week taper phase. Body composition was assessed using DEXA and ultrasound at weeks 0, 4, 8, 10, and 12. Vital signs and blood markers were assessed at weeks 0, 8, and 12. Results Significant group x time (p  < 0.05) interactions were present for cross-sectional area of the rectus femoris, which increased in TRT (+1.07 cm2 ) versus PLA (−0.08 cm2 ), as well as muscle thickness (TRT: +0.49 cm; PLA: +0.04 cm). A significant group x time (p  < 0.05) interaction existed for creatinine (TRT: +0.00 mg/dL; PLA: +0.15 mg/dL) and estimated glomerular filtration rate (TRT: −0.70 mL/min/1.73; PLA: −14.6 mL/min/1.73), which remained within clinical ranges, but no other significant observations were observed. Conclusions Supplementation with a combination of extended-release caffeine and ancient peat and apple extracts may enhance resistance training-induced skeletal muscle hypertrophy without adversely affecting blood chemistry.